Relación entre el gasto público por alumno y el nivel de educación alcanzado por la población de 15 años y más de edad de Loreto periodo 2015 – 2019 - Díaz Paredes, Julia Edith (2024)
One of the pillars of countries' development is the educational sector, so governments must dedicate an important part of the annual budget to it for its efficient functioning. The department of Loreto is one of the largest in the country and has a large population dispersion, which makes the implementation of public policies difficult. This research is Quantitative, Correlational level and Non-Experimental design. The conclusions reached are: public spending per student is not associated with the educational level achieved by the population of Loreto aged 15 and over, belonging to the period 2015 - 2019, having achieved a Correlation Coefficient of r = 0.629843387 and a Coefficient of Determination of R2 = 0.396702692. The highest average public expenditure per student in Loreto was dedicated to Higher University Education, which was S/. 8,669.00; highlighting that the universities went through a licensing process where the government allocated a larger budget to equip them so they could qualify. The population of Loreto aged 15 and over has mainly reached the level of Secondary Education, concentrating on average 45.75% of the total. The next educational level reached was Primary Education with 30.76%. The expenditure carried out by the Regional Directorate of Education of Loreto had an increasing behavior year after year, increasing on average by 9.06% annually.